1976
DOI: 10.7589/0090-3558-12.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Premature Parturition in the California Sea Lion

Abstract: Twenty percent of the California sea lion pups born on San Miguel Island die due to premature parturition. Specimens collected from premature-partus animals resulted in recovery of a virus, San Miguel Sea Lion Virus, indistinguishable from Vesicular Exanthema of Swine Virus, and Leptospira pomona from some of the premature cows and pups. The age range of 10 females delivering healthy pups in June was 10-14 years. With one exception, the ages in 10 aborting females was 6-8 years. The p,p'-DDE levels of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 19 publications
1
52
1
1
Order By: Relevance
“…1). In the late 1970s, a high proportion (20%) of California sea lion pups born on the island were reported to die following premature parturition (Gilmartin et al, 1976). Higher concentrations of the organochlorine contaminants dichloro-diphenyl-trichloroethane (DDT) and polychlorinated biphenyls (PCB) were found in tissues from premature parturient dams and their pups than those measured in full-term dam-pup pairs (DeLong et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…1). In the late 1970s, a high proportion (20%) of California sea lion pups born on the island were reported to die following premature parturition (Gilmartin et al, 1976). Higher concentrations of the organochlorine contaminants dichloro-diphenyl-trichloroethane (DDT) and polychlorinated biphenyls (PCB) were found in tissues from premature parturient dams and their pups than those measured in full-term dam-pup pairs (DeLong et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…California sea lions are persistently exposed to serovar Pomona during nonoutbreak years (15). Intermittent exposure of California sea lions to the same L. interrogans serovar Pomona clonal population from another host species through accidental exposure over a 37-year period is unlikely (1,4,6,7,(10)(11)(12)(13)23). We conclude that California sea lions are maintenance hosts of L. interrogans serovar Pomona.…”
mentioning
confidence: 99%
“…Subsequent laboratory studies showed that HAHs increased susceptibility to bacteria (42,48,61), viruses (26,50,62), and protozoan parasites (26). Several investigators suggested associations between epizootics and elevated organochlorine exposure in beluga whales (Delphinapterus leucas) in the St. Lawrence Estuary (63), California sea lions (Zalophus californianus) on San Miguel Island (64,65), harbor seals (Phoca vitulina) in Europe (66)(67)(68), and bottlenose dolphins (Tursiops truncatus) in the Atlantic Ocean (69). At highly contaminated sites in the Great Lakes, doublecrested cormorants (Phalacrocorax auritus) had increased rates of eye infections associated with Pasteurella multocida (70).…”
Section: Introductionmentioning
confidence: 99%